Assessing the Impacts of Urbanisation on Land Use Change in Zambia: A Study of Lusaka Urban District - Simooya, Steriah Monica (University of the Witwatersrand, Johannesburg, 2024)
Urbanisation is a multifaceted, transformative process and a significant global trend that has impacted societies, economies and the biophysical environment. The process of urbanisation results in various challenges as it comes with profound positive and negative effects especially for developing countries. Most countries face insurmountable urbanisation challenges as their governance processes, systems and institutions are ideally not designed to deal and cope with urbanisation processes. Lusaka urban district has been urbanising at a fast pace and, just like many developing cities in Sub-Saharan Africa, has faced various challenges. Urbanisation in Lusaka has led to shifts in urban land use, consequently posing both challenges and opportunities to urban residents. Hence, this study was an assessment of the impacts of urbanisation on land use change in Zambia, a study that was conducted in Lusaka urban district. The aim of the study was to assess the impacts of urbanisation and land use change on the urban poor and vulnerable people in Lusaka whose livelihoods have been historically dependent on land. The study further sought to establish how the urban poor and vulnerable people negotiate their rights to the city in socially and economically productive ways considering the government’s policy on the economic growth and development of the city. This study was guided by pragmatism, which is concerned with what works in solving the problem and, the solution to the problem. Pragmatism posits that the nature of knowledge is not static while knowledge generation is achieved using various methods. Mixed methods research approach was used to assess the impacts of urbanisation and land use change on urban residents in Lusaka district. Both qualitative and quantitative methods were used to collect, analyse, and interpret the study findings simultaneously. Remote sensing (from 1990-2020 for selected areas of Lusaka urban), document analysis, questionnaires, and semi-structured interviews were used as data collection tools. Probability sampling was used to come up with households while non-probability sampling was used for key respondents. A total of 922 households were drawn from the selected residential areas and 12 key respondents from ministries and agencies, Non-Governmental and Civil Society Organisations. Qualitative data were analysed using themes and regular patterns derived from the study’s naturally occurring and emerging themes to derive meaning and interpretation expressed using words and not numbers. To generate frequencies and percentages, quantitative data were analysed using excel and the Statistical Package for Social Sciences (SPSS). Remote sensed imagery was analysed using ArcGIS 10.5. Documents such as maps, and policy documents were analysed for interpretation and meaning as they provided information on land use trends, management, and the regulations guiding the use and management of land in Zambia. Theoretically, the study employed the Hoyt Sector model of urban growth and expansion to explain the outward expansion of Lusaka district along the major transportation arteries of the city. The Hoyt sector model explains land use patterns from independence (1964) up to recent times. Lusaka’s initial development was along the major transportation artery, the British South African railway line and later, the major roads of the city. The Hoyt model also helps in explaining the location of residential areas and why industries are found in defined areas plus the role of the city’s major transportation arteries. The critical urban theory was used to explain the rapid urbanisation of Lusaka city, the emerging shifts in urban land use, and the resultant impacts on urban citizens and their livelihoods. This theory does not conform to mainstream urbanisation theory that explains urbanisation in relation to urban population growth. It emphasises that urbanisation is multifaceted and dynamic, a continuous construction of urban knowledge made up of political, cultural, historical, environmental and economic organisation of any given city. Most importantly, this theory advocates for understanding and explaining of urbanisation in socially inclusive, sustainable and democratic ways. The study findings revealed that Lusaka’s urbanisation has been characterised by the expansion of the built-up area at the expense of other land use and land cover classes. This has resulted in the mushrooming and expansion of informal settlements, diminishing agricultural land, the conversion of grass, crop, and bare land into mixed urban land uses particularly settlements and commercial use. The changes in urban land use are driven by urban population growth, economic growth and development policies and processes, rural-urban migration and the consumerism behaviour characterising most urban residents. The findings further indicate that urbanisation has brought about opportunities and challenges for urban residents. Urbanisation has come with various economic opportunities such as the creation and improved access to various goods and services, employment opportunities, the global exchange and fusion of ideas, cultures, food, and entertainment. Negatively, urbanisation has exacerbated corruption, social injustice and inequality consequently affecting the urban poor who have historically depended on land for agriculture and livelihoods. It has also created the urban divide in urban areas where Lusaka is now composed of the haves and have not, the poor and affluent, informal and overcrowded settlements, and gated communities. Various forms of pollution are now rampant, there’s widespread environmental degradation resulting in environmental ills such as deforestation, climate change, and shortage of resources. These have presented insurmountable challenges for the achievement of sustainable urban development. Furthermore, the diminishing agricultural land is a huge challenge impacting urban food security and urban livelihoods. This is further making it difficult to achieve Sustainable Development Goals particularly SDG no.11 on sustainable and inclusive cities and Africa’s Agenda 2063. The study concludes that significant changes in land use have occurred to urban land in the Lusaka district attributed mainly to urbanisation processes and urban population increase. The changes have mainly been from bare, crop, and grassland to built-up for settlements and commercial purposes, and various ecosystem goods and services have been lost in the process. This has greatly affected the urban poor and vulnerable whose livelihoods depended on agriculture and as such, are struggling to cope with the developments. The study concludes that human settlements are a key driver of urban land use change in Lusaka district. The study recommends that policy formulation, implementation, monitoring, and evaluation be prioritised to sustainably develop the district and manage its land use. The study also recommends the need to involve all stakeholders in the entire process so that policies reflect their various needs. All these challenges pose as infringements to urban livelihoods that are particularly felt by the urban poor and vulnerable people living in Lusaka urban district. The study contributes to the body of knowledge by providing insights into the impacts of urbanisation, land use change and management, urban population growth, urban food security, and urban livelihoods. These are all prerequisites to the achievement of SDGs particularly no.11 on sustainable cities and Africa’s Agenda 2063, the blueprint for the continent’s sustainable development. The study will provide insights that will help policy and decision makers and all concerned stakeholders in the re-planning of land use change in Lusaka district to allocate resources to where they are most needed. The study will help policy and decision makers to come up with environmentally sustainable land use and management policies that do not degrade the environment, expose and leave urban livelihoods vulnerable particularly the urban poor and vulnerable groups not just in Lusaka but in other Sub-Saharan African cities with similar but complex urban spatial landscapes.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Urbanisation; Land Use Change; Urban Population Growth; Urban Poor and Vulnerable; Land Power Relations; Rights to the City; Coping Strategies; UCTD; SDG-11: Sustainable cities and communities; SDG-9: Industry, innovation and infrastructure